IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PENDIDIKAN DI SMP NEGERI 4 SIAK HULU KABUPATEN KAMPAR - GUSRIANI GUSRIANI; MUHAMMAD NASIR; SUARMAN SUARMAN (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This research aims to analyse the implementation of information systemmanagement of education in state junior high school 4 siak hulu the district kampar, referring tomanagement functions namely: (1) the planning; (2) the organizing; (3) the implementation; (4)evaluation of information systems management education. The implementation of informationmanagement system analyzed from the aspect of: (1) of communication, (2) the resources, (3)of implementing attitude, and (4) bureaucratic structure, based on the implementation of policymodel according to edward. This research use descriptive of qualitative methods.Data takenthrough interviews, observation, and documentation. The research results show that: (1) ofinformation received in decision-making process in the state junior high school 4 Siak Huluupstream not yet fully on time. (2) the resources, such as human resources, resources hardware,resources software and data management processes become information very helpful in theprocess of management. Because resources affected the implementation of information systemsmanagement education in state junior high school 4 siak hulu the district kampar. Usinginformation systems in the management of data and data collection students will be moreeffective and efficient compared with the management of manually.